Construction and Validation of Evaluation Instruments for Science Learning Programs Based on Context, Input, Process, And Product (CIPP) Models - Cindy Alvianita; Tanti Tanti; Bambang Hariyadi (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to develop an evaluation instrument for science learning program in junior high schools based on the CIPP (Context, Input, Process, Product) evaluation model. This research uses the exploratory sequential mix method for instrument development. The qualitative stage was carried out through in-depth interviews with five principals and ten teachers. The qualitative stage aims to analyze needs in the field and explore the opinions of school principals and teachers regarding the evaluation of science learning programs. Researchers distributed instruments to 112 participants for the quantitative stage of the validation test. The instrument was validated in three stages. The first stage is the face validity test, the second stage is the Exploratory Factor Analysis (EFA) test, and the last stage is the Confirmatory Factor Analysis (CFA) test. The results of face validity conducted with two experts stated that each indicator developed had followed the flow of the Context, Input, Process, and Product (CIPP) model. Exploratory Factor Analysis Test Based on scree plot data, it was found that there was a fault after the four components, and the researcher decided to take four elements with a total variance of 50.95%. The confirmatory Factor Analysis (CFA) test showed that from 47 items, only 35 items were declared valid. This research has positive implications for the practice of integrated science learning at the junior high school level in Indonesia. Principals and teachers can use this CIPP-based evaluation instrument to evaluate the effectiveness of the integrated science learning process that has been carried out so far